Sphene and Zircon Fission Track Analysis of Syenite Rocks of the Sushina Hills, Purulia-Bankura Shear Zone (TPSZ) - Ghosh, Amal Kumar (International Journal of Geography and Geology, 2018)
Sushina hills are situated in the Purulia-Bankura Shear Zone. This is tectonically disturbed narrow zone nearly 100 Km long having WNW-ESE trend. Two different rock assemblages namely Chhotanagpur Gneissic Complex and rocks of Singhbhum Group occur on the two sides of this shear zone. In this paper, I have used fission track ages of two cogenetic minerals and their corresponding closure temperatures to describe the denudation history. The difference of their fission track ages provides the rate of denudation 4 m/Ma during the period 970Ma-1458Ma due to tectonic activity. The youngest age of zircon of 970Ma represents the timing of the initiation of denudation.